Perilaku pencegahan Covid-19 pada ibu rumah tangga di Kota Subulussalam - Yesika Amananda; Farrah Fahdhienie; Agustina Agustina (Jurnal SAGO Gizi dan Kesehatan, 2022)
Background: Coronavirus Disease (Covid-19) is a new type of contagious disease that was first discovered in Wuhan, China, on December 31st, 2019. The government has set various prevention efforts such as carrying out 5M prevention behaviors (wearing masks, washing hands, keeping a distance, staying away from crowds, and reducing mobility). Housewives are essential in preventing Covid-19 and protecting families from this disease.Objectives: This study aims to determine factors related to Covid-19 prevention behavior in housewives in Sukamakmur Village, Simpang Kiri District, Subulussalam City.Methods: The design used in the study is cross-sectional, through interviews using a questionnaire with a sample of 80 respondents, which was carried out on March 9-18, 2022. Statistical analysis using the Chi-Square test at 95% CI.Results: The results showed that respondents with less preventive behavior were 65%, basic education level was 47,5%, poor knowledge was 45%, the negative attitude was 52,5%, and negative stigma was 56,3%. The results of the bivariate analysis showed that there was a relationship between education level (p= 0,001), knowledge (p= 0,001), attitude (p= 0,001), and stigma (p= 0,001) with 5M behavior in preventing Covid-19.Conclusion: The level of education, knowledge, attitudes, and stigma of housewives is related to 5M behavior in preventing Covid-19 in Sukamakmur Village.